Future atherosclerotic cardiovascular disease in systemic lupus erythematosus based on CSTAR (XXVIII): the effect of different antiphospholipid antibodies isotypes - Huang, Can; Ding, Yufang; Chen, Zhen; Wu, Lijun; Wei, Wei; Zhao, Cheng; Yang, Min; Lin, Shudian; Wang, Qian; Tian, Xinping; Zhao, Jiuliang; Li, Mengtao; et al. (BMC medicine, 2025)
Patients with systemic lupus erythematosus (SLE) suffered from an increasing risk of cardiovascular diseases. In this multi-center prospective study, we aimed to determine the association between antiphospholipid antibodies (aPLs) and future atherosclerotic cardiovascular disease (ASCVD) in SLE. In total, 1573 SLE patients were recruited based on the Chinese SLE Treatment and Research group (CSTAR) registry. aPLs profile, including anticardiolipin antibodies (aCL) IgG/IgM, anti-β2 glycoprotein I antibodies (aβ2GPI) IgG/IgM, and lupus anticoagulant (LA), were measured in each center. Future ASCVD events were defined as new-onset myocardial infarction, stroke, artery revascularization, or cardiovascular death. Among the 1573 SLE patients, 525 (33.4%) had positive aPLs. LA had the highest prevalence (324 [20.6%]), followed by aCL IgG (249 [15.8%]), aβ2GPI IgG (199 [12.7%]). 116 (7.37%) patients developed ASCVD during the mean follow-up of 4.51 ± 2.32 years and 92 patients were aPLs positive. In univariate Cox regression analysis, both aPLs (HR = 7.81, 95% CI 5.00-12.24, p < 0.001) and traditional risk factors of cardiovascular disease were associated with future ASCVD events. In multiple Cox regression analysis, aCL IgG (HR = 1.95, 95% CI 1.25-3.00, p = 0.003), aCL IgM (HR = 1.83, 95% CI 1.03-3.20, p = 0.039), and LA (HR = 5.13, 95% CI 3.23-8.20, p < 0.001) positivity remained associated with ASCVD; traditional risk factors for ASCVD, including smoking, gender, age and hypertension, also play an independent role in SLE patients. More importantly, Aspirin can reduce ASCVD risk in SLE patients with positive aPLs (HR = 0.57 95% CI, 0.25-0.93, P = 0.026). SLE patients with positive aPLs, especially positive aCL IgG/IgM and LA, warrant more care and surveillance of future ASCVD events during follow-up. Aspirin may have a protective effect on future ASCVD.